Biochar-based impermeable cement mortar and preparation method thereof

By adding pyrolytic carbonization treatment biochar to cement, the anti-seepage performance and carbon storage capacity of building materials are improved, and the problem of insufficient anti-seepage performance of carbon neutral and cement materials in the construction industry is solved, achieving more efficient carbon storage and mechanical properties improve.

CN119285279APending Publication Date: 2025-01-10CHINA MCC5 GROUP CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411337109.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The construction industry faces challenges in achieving carbon neutrality. In the prior art, carbon removal in the air and inhibiting natural carbon removal are rarely used in the field of building materials, and the anti-seepage performance of traditional cement materials is insufficient.

Method used

Biochar is prepared by pyrolysis and carbonization treatment of plant straw, tobacco leaves and wood, and added it to cement to form biochar-based anti-seepage cement sand, improving the anti-seepage performance and carbon storage capacity of cement.

Benefits of technology

By improving the compactness and anti-seepage properties of cement, the carbon neutrality goal of the construction industry is achieved, and the mechanical properties of cement materials are improved, including compressive strength and crack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285279A_ABST
    Figure CN119285279A_ABST
Patent Text Reader

Abstract

The invention provides biochar-based impermeable cement mortar and a preparation method thereof, and relates to the technical field of building materials. The impermeable cement mortar is prepared from the following raw materials: 1 part of cement, 3 parts of sand and 0.5 part of water, the cement contains 1 to 5 weight percent of biochar. According to the method, plant straw, tobacco leaves and wood are treated in a pyrolysis carbonization mode, and greenhouse gas is not additionally discharged outwards in the production process; the prepared biochar is an efficient carbon sequestration material, the biochar-based negative carbon cement is prepared by adding the biochar into a cement material, and the biochar-based negative carbon cement is applied to engineering, so that carbon neutralization in the building industry can be realized in an assisted manner. And the porous biochar has a huge specific surface area, provides cement hydration nucleation sites, accelerates cement hydration, improves the cement hydration degree, further improves the compactness of hardened cement paste, and improves the strength and anti-seepage performance, so that the porous biochar can be used for improving the anti-seepage performance of traditional cement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to a biochar-based anti-seepage cement mortar and a preparation method thereof. Background Art

[0002] With the implementation of the national "dual carbon" strategy, the construction industry faces huge challenges and opportunities. On the one hand, the construction industry needs to actively respond to national policies, promote the research and development and application of green and low-carbon technologies, and reduce energy consumption and carbon emissions; on the other hand, the construction industry is also actively developing new carbon neutrality paths to offset carbon emissions in the construction industry.

[0003] Negative carbon technology generally refers to the technology of capturing, utilizing and storing carbon dioxide. There are two main ways to achieve carbon removal: one is based on nature, that is, using biological processes to increase carbon removal and store it in forests, soil or wetlands; the other is through technical means, that is, directly removing carbon from the air or inhibiting the natural carbon removal process to accelerate carbon storage.

[0004] However, there are relatively few applications of removing carbon from the air or inhibiting natural carbon removal in the field of building materials. Summary of the invention

[0005] The purpose of this application is to provide a biochar-based anti-seepage cement mortar and a preparation method thereof, which can improve the anti-seepage performance of the cement material itself on the basis of helping to "reduce carbon".

[0006] The purpose of this application is achieved through the following technical solutions:

[0007] On the one hand, the present application provides a biochar-based anti-seepage cement mortar, the raw materials of which include cement, sand and water; the cement contains 1-5wt% of biochar.

[0008] On the other hand, the present application provides a method for preparing biochar-based anti-seepage cement mortar, comprising the following steps:

[0009] S1, obtaining biochar by crushing, drying, pyrolyzing and cooling the charcoal raw materials;

[0010] S2. Grind the biochar and add it to cement in proportion, then mix it with sand and water to obtain biochar-based anti-seepage cement mortar.

[0011] Beneficial effects of this application:

[0012] 1. This application uses pyrolysis carbonization to process plant straw, tobacco leaves and wood. Compared with the traditional combustion method to prepare biochar, the process of this application does not emit additional greenhouse gases during the production process; the prepared biochar is a highly efficient carbon-fixing material, which is added to cement materials to prepare a biochar-based negative carbon cement, and applied to engineering projects, which can help achieve "carbon neutrality" in the construction industry.

[0013] 2. The porous biochar prepared by pyrolysis carbonization in the present application has a huge specific surface area, provides cement hydration nucleation sites, accelerates cement hydration, improves the degree of cement hydration, and thereby increases the density of the hardened cement slurry, and its strength and anti-seepage performance are also improved accordingly. Therefore, it can be used to improve the anti-seepage performance of traditional cement.

[0014] The aforementioned main scheme of the present application and its further options can be freely combined to form multiple schemes, all of which are schemes that can be adopted and claimed for protection in the present application; and in the present application, (non-conflicting options) can also be freely combined with each other and with other options. After understanding the scheme of the present application, those skilled in the art can understand that there are many combinations based on the prior art and common knowledge, all of which are technical schemes to be protected by the present application, and they are not exhaustively listed here. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a flow chart of the biochar production process of Example 1 of the present application. DETAILED DESCRIPTION

[0016] The following non-limiting examples are provided to illustrate the present application.

[0017] A biochar-based anti-seepage cement mortar, the raw materials of which include cement, sand and water; the cement contains 1-5wt% of biochar.

[0018] In some embodiments of the present application, the mass ratio of the cement, sand and water is 1:3:0.5.

[0019] In some embodiments of the present application, the particle size of the above-mentioned biochar is greater than 40-200 mesh, the molar ratio of hydrogen content to organic carbon content in the biochar H / Corg is less than 0.7, and the molar ratio of oxygen content to organic carbon content O / Corg≤0.3.

[0020] A method for preparing biochar-based anti-seepage cement mortar comprises the following steps:

[0021] S1, obtaining biochar by crushing, drying, pyrolyzing and cooling the charcoal raw materials;

[0022] S2. Grind the biochar and add it to cement in proportion, then mix it with sand and water to obtain biochar-based anti-seepage cement mortar.

[0023] In some embodiments of the present application, the charcoal raw material in the above-mentioned step S1 includes at least one of corn stalks, tobacco waste and wood, the tobacco waste is waste tobacco stems and waste tobacco leaves, and the length or diameter after crushing is ≤5 cm.

[0024] In some embodiments of the present application, the drying temperature in the above step S1 is 150-200° C., and the drying is performed until the moisture content is ≤20%.

[0025] In some embodiments of the present application, the pyrolysis in the above-mentioned S1 step includes drying, pre-carbonization, carbonization and combustion steps in sequence; wherein the drying temperature is 100-160°C, and the drying time is 80-100min; the pre-carbonization temperature is 160-280°C, and the pre-carbonization time is 120-180min; the carbonization temperature is 280-450°C, and the carbonization time is 180-240min; the combustion temperature is 450-1000°C, preferably >700°C, and the combustion time is 60-80min.

[0026] Traditional biochar is charcoal with extremely rich carbon content, which refers to a type of refractory, stable, highly aromatic, carbon-rich solid material produced by high-temperature slow pyrolysis (usually <700°C, the target product is charcoal) in the absence of oxygen, so it is generally used as fuel. The biochar of the present application is produced by high-temperature pyrolysis (>700°C) in a non-anaerobic environment. It is a porous material with high specific surface area and high adsorption properties, so it has better carbon collection and storage effects.

[0027] In some embodiments of the present application, the cooling in the above step S1 is performed by room temperature cooling or water cooling.

[0028] In some embodiments of the present application, the above-mentioned S2 step is specifically to first add biochar and cement into water, stir at a low speed, then add sand while stirring, perform high-speed stirring, stop stirring, and stir at a high speed for the second time to obtain biochar-based anti-seepage cement mortar.

[0029] In some embodiments of the present application, the speed of the above-mentioned low-speed stirring is 60-100r / min, and the stirring time is 29-31s; the speed of the high-speed stirring is 300-350r / min, and the stirring time is 29-31s; the stirring stop time is 90s; the speed of the secondary high-speed stirring is 200-250r / min, and the stirring time is 59-61s.

[0030] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0031] Example 1

[0032] A biochar-based anti-seepage cement mortar, the preparation method is as follows:

[0033] S1, using corn stalks as charcoal raw material, Figure 1 The production process is processed: first broken into pieces with a length of ≤5cm, then low-temperature drying at a temperature of 180℃, and impurities are separated to meet production needs. The moisture content of the dried corn stalk segment is ≤20%; then it is sent to the carbonization kiln for carbonization. Drying is the first stage of the carbonization process. The semi-finished biochar is gradually dried at a temperature of 120℃ in the carbonization kiln. White water vapor is generated in the carbonization kiln, and low-molecular volatiles are gradually decomposed. Next, in the pre-carbonization stage, the temperature is controlled at about 240℃ for 150min. At this stage, the bonds of organic macromolecules break and the unstable component hemicellulose begins to decompose. In the carbonization stage, the temperature is controlled at 290-400℃ for 200min. At this stage, cellulose, lignin, etc. begin to decompose violently, and the emitted substances include wood tar, carbon monoxide, methane and other gases. In the combustion stage, the temperature is controlled at 800-900℃ and the combustion time is 80min. At this time, the pyrolysis process is basically over, and basically no gas is generated. The volatile matter remaining on the surface of the charcoal is mainly discharged to increase the fixed carbon content. The output of the pyrolysis combustion process is only biochar, and the pyrolysis gas is reused during the pyrolysis process. After the char is produced, it enters the cooling furnace for cooling to obtain the biochar product, which is finally packaged and the dust is treated by the filter cartridge dust removal method.

[0034] S2. Grind the biochar to ensure that the biochar passes through a 40-mesh sieve, and analyze the organic elements to determine that the molar ratio of the hydrogen content to the organic carbon content of the biochar is H / Corg (molar) <0.7, and the molar ratio of the oxygen content to the organic carbon content is O / Corg (molar) ≤0.3; then add the biochar to the cement at a replacement ratio of 3wt% to obtain mixed cement. Weigh or measure 450g mixed cement, 1350g standard sand and 225ml water; add water into the mixing pot first, then add the mixed cement, fix the pot on the fixed frame, and raise it to the working position; start the machine immediately, stir at a low speed of 80r / min for 30s, and at the beginning of the second 30s, evenly add the sand, adjust the mixer to a high speed of 300r / min and stir for another 30s; stop stirring for 90s, within 15s of the start of stopping stirring, put down the mixing pot, scrape the mortar on the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed of 200r / min for 60s.

[0035] S3. Immediately after the preparation of the mortar, the molding is carried out: the empty test mold and the mold sleeve are fixed on the vibration table, the mortar on the pot wall is cleaned into the pot with a material spoon, and the mortar is turned and stirred to make it more uniform. When molding, the mortar is loaded into the test mold in two layers. When loading the first layer, about 300g of mortar is placed in each groove. First, the mortar is moved along the length of the test mold with a material spoon to fill the mold grooves, and then a large distributor is vertically mounted on the top of the mold sleeve to level the material layer along each mold groove once, and then vibrate 60 times. Then load the second layer of mortar, and use a material spoon to move the mortar along the length of the test mold to fill the mold grooves, but it cannot touch the vibrated mortar, and then use a small distributor to level it and vibrate 60 times. Remove the mold sleeve, remove the test mold from the vibration table, and use a metal straight edge ruler to mount it at one end of the top of the test mold at an angle of approximately 90°, and then slowly move to the other end along the length of the test mold with a horizontal sawing action to scrape off the mortar that exceeds the test mold.

[0036] The biochar-based anti-seepage cement mortar of this embodiment adopts standard curing: the test block is placed in a special curing box with a temperature of 20° C. and a relative humidity of more than 95% for curing for 28 days.

[0037] Example 2

[0038] A biochar-based anti-seepage cement mortar, the preparation method is as follows:

[0039] S1. Use waste tobacco leaves as charcoal raw materials, first crush them into pieces with a length of ≤5cm, then dry them at a temperature of 160℃, and separate impurities to meet production needs. The moisture content of the corn stalks after drying is ≤20%; then send them to the carbonization kiln for carbonization. Drying is the first stage of the carbonization process. The semi-finished biochar is gradually dried at 150℃ in the carbonization kiln. The drying time is 100min. White water vapor is generated in the carbonization kiln, and low-molecular volatiles are gradually decomposed. Next, in the pre-carbonization stage, the temperature is controlled at 180-220℃, and the pre-carbonization time is 180min. At this stage, the bonds of organic macromolecules break, and the unstable component hemicellulose begins to decompose. In the carbonization stage, the temperature is controlled at 350-420℃, and the carbonization time is 240min. At this stage, cellulose, lignin, etc. begin to decompose violently, and the emitted substances include wood tar, carbon monoxide, methane and other gases. In the combustion stage, the temperature is controlled at 750-900℃, the combustion time is 60min, the pyrolysis process is basically completed, and basically no gas is generated. The main volatile matter remaining on the surface of the charcoal is discharged to increase the fixed carbon content. The output of the pyrolysis combustion process is only biochar, and the pyrolysis gas is reused during the pyrolysis and burning process. After the charcoal is discharged, it enters the cooling furnace for cooling to obtain the biochar product, which is finally packaged and the dust is treated by the filter cartridge dust removal method.

[0040] S2. Grind the biochar to ensure that the biochar passes through an 80-mesh sieve, and analyze the organic elements to determine that the molar ratio of the hydrogen content to the organic carbon content of the biochar is H / Corg (molar) <0.7, and the molar ratio of the oxygen content to the organic carbon content is O / Corg (molar) ≤0.3; then add the biochar to the cement at a replacement ratio of 5wt% to obtain mixed cement. Weigh or measure 450g mixed cement, 1350g standard sand and 225ml water; add water into the mixing pot first, then add the mixed cement, fix the pot on the fixed frame, and raise it to the working position; start the machine immediately, stir at a low speed of 80r / min for 30s, and at the beginning of the second 31s, evenly add the sand, adjust the mixer to a high speed of 350r / min and stir for another 30s; stop stirring for 90s, within 16s from the start of stopping stirring, put down the mixing pot, scrape the mortar on the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed of 250r / min for 60s.

[0041] S3. Immediately after the preparation of the mortar, the molding is carried out: the empty test mold and the mold sleeve are fixed on the vibration table, the mortar on the pot wall is cleaned into the pot with a material spoon, and the mortar is turned and stirred to make it more uniform. When molding, the mortar is loaded into the test mold in two layers. When loading the first layer, about 300g of mortar is placed in each groove. First, the mortar is moved along the length of the test mold with a material spoon to fill the mold grooves, and then a large distributor is vertically mounted on the top of the mold sleeve to level the material layer along each mold groove once, and then vibrate 60 times. Then load the second layer of mortar, and use a material spoon to move the mortar along the length of the test mold to fill the mold grooves, but it cannot touch the vibrated mortar, and then use a small distributor to level it and vibrate 60 times. Remove the mold sleeve, remove the test mold from the vibration table, and use a metal straight edge ruler to mount it at one end of the top of the test mold at an angle of approximately 90°, and then slowly move to the other end along the length of the test mold with a horizontal sawing action to scrape off the mortar that exceeds the test mold.

[0042] The biochar-based anti-seepage cement mortar of this embodiment adopts environmental curing: the test block is placed in indoor air conditions for curing, the temperature is between 16-24° C., and the humidity is between 40%-80%.

[0043] Experimental Example 1

[0044] In this experimental example, biochar prepared from three different carbon raw materials (corn stalks, tobacco leaves and wood) was ground to 80 mesh and prepared according to the preparation steps of biochar-based anti-seepage cement mortar in Example 1, using standard sand and standard curing conditions.

[0045] Two parallel tests were conducted, and the test of impermeability was conducted using ASTM C1585-13 "Standard Test Method for Measurement of Rate of Absorption of Water by Hydraulic-Cement Concretes" published by the American Society for Testing and Materials. The test results are shown in Tables 1 and 2.

[0046] CS is corn straw biochar, TL is tobacco leaf biochar, and WM is wood biochar.

[0047] Among them, CS-1 is the mortar specimen with 1% corn straw biochar added, TL-1 is the mortar specimen with 1% tobacco leaf biochar added, and so on.

[0048] Table 1

[0049]

[0050]

[0051] Table 2

[0052]

[0053]

[0054] It can be seen from Tables 1 and 2 that under standard sand and standard curing conditions, the cement mortar with biochar added has improved the anti-seepage performance of the material to varying degrees compared with the control group, among which TL-2 / TL-5 is the best.

[0055] In the experiment, we also found that the pore structure and large specific surface area of ​​biochar help it fill the tiny pores in concrete, improving the density and durability of concrete. Therefore, biochar can also enhance the toughness and ductility of concrete, thereby improving its crack resistance. When the amount of biochar added is less than 1%, the biochar is difficult to play a role; with the addition of biochar, the compressive strength, flexural strength and splitting tensile strength of concrete will be improved. When the replacement rate of biochar is within an appropriate range (such as less than 5%), these mechanical properties of concrete can be maintained or even better than concrete without biochar. However, too high a replacement rate (such as more than 8%) may lead to a significant decrease in mechanical properties. Therefore, this application selects 1-5wt as the optimal ratio of biochar addition.

[0056] Experimental Example 2

[0057] The preparation method and test method of this experimental example are basically the same as those of Experimental Example 1, except that environmental curing is used. The experimental results are shown in Tables 3 and 4.

[0058]

[0059]

[0060]

[0061] Table 4

[0062]

[0063] The experimental results in Table 3 and Table 4 show that under standard sand and environmental curing conditions, the cement mortar with biochar added has different degrees of improvement on the anti-seepage performance of the material compared with the control group, among which TL-5 is the best.

[0064] By comparing Experimental Example 1 with Experimental Example 2, it can be seen that the influence of curing conditions on all cement mortar specimens is relatively consistent, and under environmental curing, the anti-permeability performance of cement mortar specimens is relatively better.

[0065] Experimental Example 3

[0066] The preparation method and test method of this experimental example are basically the same as those of Experimental Example 2, except that river sand is used instead of standard sand. The experimental results are shown in Tables 5 and 6.

[0067] Table 5

[0068]

[0069]

[0070] Table 6

[0071]

[0072]

[0073] It can be seen from Tables 5 and 6 that under the conditions of river sand and environmental curing, the cement mortar with biochar added has improved the anti-seepage performance of the material to varying degrees compared with the control group, among which TL-5 is the best.

[0074] By comparing Experimental Example 2 with Experimental Example 3, it can be seen that compared with standard sand, the use of river sand is less beneficial for improving the anti-seepage performance of cement mortar.

[0075] Experimental Example 4

[0076] The preparation method and testing method of this experimental example are basically the same as those of Experimental Example 1, except that the biochar used in this experimental example is 40 mesh. The experimental results are shown in Tables 7 and 8.

[0077] Table 7

[0078]

[0079]

[0080] Table 8

[0081]

[0082]

[0083] It can be seen from Tables 7 and 8 that under standard sand and standard curing conditions, the cement mortar with biochar added has different degrees of improvement in the anti-seepage performance of the material compared with the control group, among which TL-3 / TL-5 is the best.

[0084] By comparing Experimental Example 1 with Experimental Example 4, it can be seen that the use of biochar with larger particle size is of great help in improving the anti-seepage performance of cement mortar.

[0085] The aforementioned basic examples and their further selected examples can be freely combined to form multiple embodiments, all of which are embodiments that can be adopted and claimed for protection in this application. In the scheme of this application, each selected example can be arbitrarily combined with any other basic examples and selected examples.

[0086] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A biochar-based anti-seepage cement mortar, characterized in that: The raw materials of the anti-seepage cement mortar include cement, sand and water; the cement contains 1-5wt% of biochar.

2. The biochar-based anti-seepage cement mortar according to claim 1, characterized in that: The mass ratio of cement, sand and water is 1:3:0.

5.

3. The biochar-based anti-seepage cement mortar according to claim 1, characterized in that: The particle size of the biochar is greater than 40-200 mesh, the molar ratio of hydrogen content to organic carbon content in the biochar is H / Corg<0.7, and the molar ratio of oxygen content to organic carbon content is O / Corg≤0.

3.

4. A method for preparing the biochar-based anti-seepage cement mortar according to claim 1, characterized in that: The following steps are involved: S1, obtaining biochar by crushing, drying, pyrolyzing and cooling the charcoal raw materials; S2. Grind the biochar and add it to cement in proportion, then mix it with sand and water to obtain biochar-based anti-seepage cement mortar.

5. The method for preparing a biochar-based anti-seepage cement mortar according to claim 4, characterized in that: The charcoal raw material in step S1 includes at least one of corn stalks, tobacco waste and wood, the tobacco waste is waste tobacco stems and waste tobacco leaves, and the length or diameter after crushing is ≤5 cm.

6. The method for preparing a biochar-based anti-seepage cement mortar according to claim 4, characterized in that: The drying temperature in step S1 is 150-200° C., and the drying is performed until the moisture content is ≤20%.

7. The method for preparing a biochar-based anti-seepage cement mortar according to claim 4, characterized in that: The pyrolysis in the S1 step includes drying, pre-carbonization, carbonization and combustion steps in sequence; wherein the drying temperature is 100-160°C, and the drying time is 80-100 min; the pre-carbonization temperature is 160-280°C, and the pre-carbonization time is 120-180 min; the carbonization temperature is 280-450°C, and the carbonization time is 180-240 min; the combustion temperature is 450-1000°C, and the combustion time is 60-80 min.

8. The method for preparing a biochar-based anti-seepage cement mortar according to claim 4, characterized in that: In step S1, the cooling is performed by room temperature cooling or water cooling.

9. The method for preparing a biochar-based anti-seepage cement mortar according to claim 4, characterized in that: The step S2 specifically includes first adding biochar and cement into water, stirring at a low speed, then adding sand while stirring, stirring at a high speed, stopping stirring, and stirring at a high speed for the second time to obtain biochar-based anti-seepage cement mortar.

10. The method for preparing a biochar-based anti-seepage cement mortar according to claim 9, characterized in that: The low-speed stirring speed is 60-100 r / min, and the stirring time is 29-31 s; the high-speed stirring speed is 300-350 r / min, and the stirring time is 29-31 s; the stopping time is 90 s; the secondary high-speed stirring speed is 200-250 r / min, and the stirring time is 59-61 s.